Crecimiento y maduración sexual de Astyanax fasciatus (Pisces: Characidae) en el embalse Arenal, Guanacaste, Costa Rica - Mora Jamett, Margarita (1997)
Growth and sexual maturation of Astyanax fasciatus were studied in shallow areas of the Arenal reservoir in Costa Rica. Von Bertalanffy's equation was 11 = 167.3 (l - e(-0.093 ,-0.132). The mean growth for the first six months was 11.7 mm/month, 6.9 for the six following months, and diminishing to 4.0 mmJmonth in the followin! months. The relationship between total length and weight was: W = 8.6 x 10-113.081 for males and W = 1.8 x 10 TI3.434 for females. Males and females attaln sexual maturity al TI between 70 - 80 mm, approximately when they are six months old. The species reproduces a11 year with peak activity between July and September.